The role of tonsillectomy in psoriasis treatment - Simões, João Filipe (BMJ Case Rep, 2015)
Psoriasis is a chronic and immune-mediated skin disease with a considerable negative impact on quality of life. The link between psoriasis, especially guttate psoriasis, and streptococcal infections, namely tonsillitis, has been studied for several years. Some authors have also suggested an association with other types of psoriasis, such as plaque psoriasis, which is the most common. The role of tonsillectomy in the treatment of plaque psoriasis is not consensual. This case report aims to discuss this topic. The authors intend to highlight the growing evidence of a relationship between plaque psoriasis and an infectious pathology of the otolaryngology area. A clinical case of severe chronic plaque psoriasis with exacerbations linked to acute tonsillitis is described. The case was recalcitrant to dermatological treatment and tonsillectomy was included in the treatment options. After surgery, the skin disease was evidently controlled and significant improvement on the patient's quality of life was also evident.